2015
DOI: 10.1089/ten.teb.2014.0662
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Pathways and Gene Regulatory Networks in Cardiomyocyte Differentiation

Abstract: Strategies for harnessing stem cells as a source to treat cell loss in heart disease are the subject of intense research. Human pluripotent stem cells (hPSCs) can be expanded extensively in vitro and therefore can potentially provide sufficient quantities of patient-specific differentiated cardiomyocytes. Although multiple stimuli direct heart development, the differentiation process is driven in large part by signaling activity. The engineering of hPSCs to heart cell progeny has extensively relied on establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 181 publications
1
36
0
Order By: Relevance
“…Our previous studies have shown that the cardiomyogenic activities of tri‐substituted azoles were not due to p38α MAPK inhibition but was likely to be due to the inhibition of the Wnt/β‐catenin pathway via the interaction with the CK1δ/ε during the post mesodermal stage (days 4–8) . Based on the biphasic and time dependent role of Wnt/β‐catenin signaling in cardiomyogenesis , a high‐efficiency single EB‐based cardiac differentiation method with the addition of CHIR99021 was established and employed in the present study for the preliminary screening of TIs. This was then followed by a secondary screen using a monolayer cardiac differentiation assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have shown that the cardiomyogenic activities of tri‐substituted azoles were not due to p38α MAPK inhibition but was likely to be due to the inhibition of the Wnt/β‐catenin pathway via the interaction with the CK1δ/ε during the post mesodermal stage (days 4–8) . Based on the biphasic and time dependent role of Wnt/β‐catenin signaling in cardiomyogenesis , a high‐efficiency single EB‐based cardiac differentiation method with the addition of CHIR99021 was established and employed in the present study for the preliminary screening of TIs. This was then followed by a secondary screen using a monolayer cardiac differentiation assay.…”
Section: Discussionmentioning
confidence: 99%
“…The data is presented as the mean AE SEM. cardiomyogenesis [1], a high-efficiency single EB-based cardiac differentiation method with the addition of CHIR99021 was established and employed in the present study for the preliminary screening of TIs. This was then followed by a secondary screen using a monolayer cardiac differentiation assay.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published paper has reported the importance of the exogenous addition of retinoic acid (RA) during human ESC differentiation for atrial chamber cell development [54]. Treating differentiating human ESCs with the Wnt inhibitors, IWP-4 and IWR-1, resulted in CMs with differing atrial and ventricular expression levels of, respectively, MLC-2a and MLC-2v [55]. Inhibition of the Wnt signaling pathway by using IWR-1 has been shown to differentiate human ESC-CMs towards mostly atrial-like CMs [41].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when non-canonical Wnt signaling pathway is activated through Wnt11 and Wnt5A activation, this also increases cell differentiation into cardiomyocytes (Pagliari et al, 2014 BMP-Smad1 inhibits Wnt/b-catenin and activates non-canonical Smad binding factors, leading to the transcription of activating transcription factor-2 (ATF2), while promoting major histocompatibility complex b (b-MHC) expression, contributing to heart cell differentiation (Parikh et al, 2015). Thirdly, FGF activates the PI3K/Akt signaling pathway to preserve stem cell properties (Parikh et al, 2015); moreover, via the MAPK/ERK signaling pathway they cause proliferation of cardiac progenitor cells but inhibition of their final differentiation into mature cardiomyocytes (Tirosh-Finkel et al, 2010). Repression of FGF signaling, therefore, accelerates the differentiation process of cardiac precursor cells (Tirosh-Finkel et al, 2010).…”
Section: Differentiation Of Transplanted Cells Into Heart Cellsmentioning
confidence: 99%